Temperature-Dependent Multidimensional Self-Assembly of Polyphenylene-Based "Rod-Coil" Graft Polymers - Huang, Yinjuan; Mai, Yiyong; Yang, Xianwen; Beser, Uliana; Liu, Junzhi; Zhang, Fan; Yan, Deyue; Muellen, Klaus; Feng, Xinliang (Journal of the American Chemical Society, 2015)
We present a novel type of "rod-coil" graft copolymer containing a polyphenylene backbone linked with poly(ethylene oxide) (PEO) side chains. Such graft copolymers manifest unprecedented temperature-dependent one-dimensional (1D) and two-dimensional (2D) self-assembly in solution. At 20 °C, which is higher than the crystallization temperature (Tc) of the PEO chains, the achiral graft copolymers self-organize into nanoribbons that twist into 30 μm ultralong helices with controlled pitch depending on the grafting ratio of the PEO chains. At 10 °C, which is lower than the Tc, quadrangular multilayer sheets of over 10 μm in lateral size are obtained. To our knowledge, this work presents the first example of controlled self-assembly of graft polymers into 1D helix and 2D sheet superstructures.
CRIS-Team Scopus Importer:2023-03-20